Determinan Perilaku SADARI Remaja Putri Dalam Upaya Deteksi Dini Kanker Payudara di SMK Negeri 8 Medan Tahun 2014 - yenni sari; Namora Lumongga Lubis; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Breast cancer is a disease that occurs due to abnormal growth of cells in the breast tissue if not sooner in the handle will cause death. According to Riskesdas (2009), the highest cancer afflicting Indonesia women's breast cancer incidence by number 26 per 100,000 women. While according to SIRS (2011), breast cancer ranks first on the inpatient cancer patients throughout the hospital in Indonesia (16,85%). The purpose of this research is to know the relationship between the determinants of behavior breast self-examination (BSE) young women in SMK Negeri 8 Medan by 2014. Factors which affect, among others, age, family disease history, knowledge, attitude, and the nearest source of information. Type of this research is quantitative research is deskritif. The population in this research is the young women who attend school in SMK Negeri 8 Medan and samples taken as many as 89 people. Sampling techniques that used for stratified random sampling. Data obtained through interviews with a questionnaire and analyzed using Independent Test Sample Test and Chi-square. Based on the research found that there was an association ( p < 0,05 ) between the ages of with the act of breast self - examination (BSE), would be aware of between the acts of family sickness with the act of breast self - examination (BSE) , would be aware of between knowledge by the act of breast self - examination (BSE), would be aware of bet breast self - examination (BSE), ween attitude with the act of breast self - examination (BSE), would be aware of between a source of information with the act of breast self - examination (BSE) and between persons nearest to the act of breast self - examination (BSE). According to research above and suggested to dept. of health and puskesmas to increase promotion of health on the dangers of breast cancer and important realize to women especially teenage girls. Keywords : Determinan, behavior, breast self-examination (BSE)